2015
DOI: 10.1515/intox-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Cupressus sempervirens extract against indomethacin-induced gastric ulcer in rats

Abstract: Cupressus sempervirens (C. sempervirens) belongs to the family Cupressaceae. It is widspread in Northern Africa, Greece, Turkey, North America, Cyprus and Syria. Cupressuflavone is the major ingredient of the plant leave extract. The aim of the present study was to evaluate the antiulcerogenic activity of the extract of C. sempervirens leaves in gastric ulcer tissues induced by indomethacin. The results of the present study revealed that indomethacin significantly decreased glutathione S-transferase (GST), glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Our data supports other studies that showed that health beneficial effects as antioxidant and anti-inflammatory effects can be achieved using plant–derived flavonoids [60,61]. This can be achieved by modulation of gene expression of certain proteins involved in the inflammatory response and alteration of activity levels of enzymes involved in antioxidant response [26].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our data supports other studies that showed that health beneficial effects as antioxidant and anti-inflammatory effects can be achieved using plant–derived flavonoids [60,61]. This can be achieved by modulation of gene expression of certain proteins involved in the inflammatory response and alteration of activity levels of enzymes involved in antioxidant response [26].…”
Section: Discussionsupporting
confidence: 91%
“…Sempervirens extract administration protected against indomethacin-induced gastric ulcer. Such protection was associated with increased SOD activity [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Koriem et al reported that cupressuflavone, a flavonoid found in C. sempervirens showed dose-dependent antiulcerogenic activity on gastric ulcer. 11 Other major components of this plant include amenoflavone, rutin, quercetin and myricitrin flavonoids which also show antioxidant activities. 12 In addition, the leaf extract of C. sempervirens is used for the treatment of gastrointestinal disorders 13 and stimulates accelerated action on slow-healing wounds.…”
Section: Discussionmentioning
confidence: 99%